BRINGING DEMOCRACY TO LIFE IN THE CLASSROOM: IMPLEMENTATION OF PKN IN FORMING STUDENTS' NATIONALIST ATTITUDES AT SDN 091482 KASINDIR - Surya Novalina Panjaitan; Dewa Bagus Sanjaya; I Nengah Suastika (RADJA PUBLIKA, 2026)
Civics education faces threats from globalization and moral decadence. This study aims to analyze the implementation of Civics as a democratic education at SDN 091482 Kasindir and its contribution to the formation of students' nationalist attitudes. Using a qualitative approach with a single case study design, data were collected through a literature review, participant observation (12 Civics meetings in grades 4, 5, and 6), and interviews with 3 teachers, the principal, and 15 students. Data analysis used the Miles & Huberman interactive model. The results show that the implementation of Civics as a democratic education is realized through three main practices: deliberative discussions on national issues, simulations of joint decision-making, and collaborative projects of patriotism. The nationalist attitudes formed include pride as Indonesian citizens, a willingness to prioritize common interests, participation in simple national defense activities: ceremonies, mutual cooperation, and respect for national symbols. The main obstacles are limited time and teachers' understanding. This study contributes to the development of a nationalism-based democratic education model in elementary schools.